New Growth Drivers for Low-Income Countries : The Role of the BRICs. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The emergence of BRICs-Brazil, Russia, India, and China-is reshaping low-income countries' (LICs) international economic relations. While industrial countries remain LICs' dominant development partners, LIC-BRIC ties have increased so rapidly over the past decade that BRICs have become new growth drivers for LICs. Trade with BRICs is already close to half of the value of combined trade with the European Union and the United States, and larger than with other emerging market economies. BRIC FDI and development financing are making a significant impact in some key areas despite their relatively small volumes compared with those from advanced countries. Beyond the increased flows of goods and capital, BRICs have brought new dynamics in LICs' economic relations with the rest of the world, complementing as well as competing with OECD partners. Nevertheless, while potential benefits from the LIC-BRIC ties are enormous, there are challenges and risks in realizing such benefits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet